Switching on oxygen activation by cobalt complexes of pentadentate ligands. - Vad, MS; Nielsen, A; Lennartson, A; Bond, A; McGrady, J; McKenzie, C (2011)
The monoanionic N(4)O ligand N-methyl-N,N'-bis(2-pyridylmethyl)ethylenediamine-N'-acetate (mebpena(-)) undergoes oxidative C-N bond cleavage in the presence of Co(II) and O(2). The two resultant fragments are coordinated to the metal ion in the product [Co(III)(2-pyridylformate)(mepena)]ClO(4) (mepena(-) = N-methyl-N'-(2-pyridylmethyl)ethylenediamine-N'-acetato). Bond cleavage does not occur in the presence of chloride ions and [Co(III)(mebpena)Cl](+), containing intact mebpena(-), can be isolated. The oxidative instability of the mebpena(-) in the presence of Co(II) and air stands in contrast to the oxidative stability of the family of very closely related penta- and hexa-dentate ligands in their cobalt complexes. Cyclic voltammetry on the matched pair [Co(III)Cl(mebpena)](+) and [Co(II)Cl(bztpen)](+), bztpen = N-benzyl-N,N',N'-tris(2-pyridylmethyl)ethylenediamine, shows that substitution of a pyridine donor for a carboxylato donor results in a relatively small cathodic shift of 150 mV in the E°(Co(II)/Co(III)) oxidation potential, presumably this is enough to determine the contrasting metal oxidation state in the complexes isolated under ambient conditions. DFT calculations support a proposal that [Co(II)(mebpena)](+) reacts with O(2) to form a Co(III)-superoxide complex which can abstract an H atom from a ligand methylene C atom as the initial step towards the observed oxidative C-N bond cleavage.